Analisis Pengaruh Tingkat Pendidikan dan Ekonomi Keluarga terhadap Perilaku Konsumtif Anak di Kelurahan Mayangan Kota Pasuruan - Safirah Rahayaan; Sugeng Pradikto (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
The aim of this research is to find out how children's purchasing habits in Mayangan Village, Panggung Rejo District, Pasuruan City are influenced by the family's economic situation and level of education. Many factors, such as parents' education level and family financial situation, can influence children's consumption habits and preferences for products and services. One hundred respondents who were parents and children in Mayangan Village were given questionnaires and survey methodology as part of the quantitative methodology used in this research. Based on the study's findings, children's purchasing habits are strongly influenced by their parents' level of education, and more educated parents often have a greater awareness of the importance of controlling consumption and how it affects children's lifestyles. Children's consumption levels can also be influenced by the economic circumstances of their families; families with higher incomes are more likely to meet their children's consumption needs, while families with lower incomes usually have tighter spending controls. Therefore, it is hoped that the government and society will pay more attention to improving the quality of education and the economic conditions of families in order to create a generation that is wiser in managing consumption and their needs. This research concludes that the two factors, namely the level of parental education and the family's economic conditions, have a significant influence on children's consumer behavior.